Environmental and Individual Determinants of Female Entrepreneurship in Algeria: Applying the Structural Equation Modeling - Abderrezzak Benhabib; Amina Merabet; Mohamed Benachenhou; Yamina Grari; Fouzi Boudia; Hadjira Merabet (Entrepreneurial Business and Economics Review)
On the basis of the seminal work of Fishbein and Ajzen (1975), we try to clarify how individual and environment factors influence the students’ attitudes towards Entrepreneurship and Entrepreneurial Intention.